1992
DOI: 10.1093/ajcn/56.4.656
|View full text |Cite
|
Sign up to set email alerts
|

Gastric capacity, gastric emptying, and test-meal intake in normal and bulimic women

Abstract: The role of the stomach in regulating appetite in bulimia nervosa was examined. Subjects were nine normal and nine bulimic women of similar age, height, and weight. Gastric capacity was estimated by filling a balloon in the stomach. The mean stomach capacity of bulimic subjects was significantly larger than that of normal subjects, as revealed by the larger balloon volume tolerated (P less than 0.01) and by the larger volume needed to produce a 5 cm H2O increase in intragastric pressure (P = 0.07). The intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(90 citation statements)
references
References 14 publications
0
87
0
1
Order By: Relevance
“…While liquids empty from the stomach at a faster rate than do solids, viscous solutions with particles of varying size may differentially influence gastric distension and gastric emptying rate (Read & Houghton 1989, Vincent et al, 1995. Increased gastric distension and decreased rate of gastric emptying have been shown to be associated with enhanced sensations of satiety (Geliebter et al, 1992). Some studies have shown that consuming pureed tomato soup before a meal can increase gastric distension and decrease the rate of gastric emptying, resulting in increased satiety compared to consuming nothing prior to the meal (Cecil, Francis, & Read, 1998;Spiegel et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…While liquids empty from the stomach at a faster rate than do solids, viscous solutions with particles of varying size may differentially influence gastric distension and gastric emptying rate (Read & Houghton 1989, Vincent et al, 1995. Increased gastric distension and decreased rate of gastric emptying have been shown to be associated with enhanced sensations of satiety (Geliebter et al, 1992). Some studies have shown that consuming pureed tomato soup before a meal can increase gastric distension and decrease the rate of gastric emptying, resulting in increased satiety compared to consuming nothing prior to the meal (Cecil, Francis, & Read, 1998;Spiegel et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Binge eating might play a particularly insidious role in obesity promotion because it putatively leads to physiological changes that increase the likelihood that binge eating will persist over time. Research suggests that binge eating results in an enlarged stomach capacity (Geliebter et al, 1992), which could increase the likelihood of future binge eating through two mechanisms. First, because stomach distension activates gastric stretch receptors and mechanoreceptors that transmit satiety signals (Goldfein, Walsh, LaChausee, Kissileff, & Devin, 1993), an individual with an enlarged stomach will consume more calories before the body initiates satiety signals to terminate eating.…”
mentioning
confidence: 99%
“…Large test meals consumed by patients have been found to produce satiety levels similar to those produced by small test meals consumed by control subjects (Geliebter et al, 1992). Regardless of whether a soup that patients had consumed was high or low in calories, the reports of fullness of BN patients at a subsequent meal did not vary.…”
Section: Hunger and Satietymentioning
confidence: 79%
“…These patients exhibited a larger-than-normal gastric capacity, even though they did not differ from control subjects in body weight, body fat, or muscle (Geliebter et al, 1992). Distention of the stomach is important in inducing feelings of satiety, and large stomach capacity (which may be increased by repeated binge eating) may help perpetuate binge eating.…”
Section: Metabolic Abnormalitiesmentioning
confidence: 83%
See 1 more Smart Citation